Revealing social values in the context of peer-to-peer energy sharing: A methodological approach - Pires Klein, Lurian (2021)
Peer-to-peer (P2P) energy sharing models fundamentally thrive on the social interconnectedness among end-users, but the literature fails to provide fit-for-purpose methodologies that uncover their Social Sciences & Humanities aspects. Therefore, this paper devised the first overarching social values-based assessment framework that allows the identification of underlying social values associated with these models. Thence, this paper looks at whether social values emerge from the ground up due to P2P energy sharing, or whether existent social values are reinforced/modified by P2P energy sharing. The impact of the framework on 123 end-users from 3 real-life pilots is analysed. The social values enacted in this paper were mainly categorised as existing social values that were reinforced by peer-to-peer energy sharing. This framework is scalable, provided that result interpretations undergo a cohesive validity check on a case-by-case basis. In conclusion, this paper expects to create a new social values-based language that is explicitly associated with P2P energy sharing.